Multidimensional analysis of factors affecting students' employment - Irina Kiryushina, Olga Shavandina, Anton Vasilev, Tatjana Philippova, (Opción, 2019)
This article concerns the problems that students face when they increase their workload at a higher educational institution by engaging in labor activities via comparative qualitative research methods. As a result, self-fulfillment is a complex and lengthy process that resides in the awareness of one’s own potential and in its embodiment in the chosen kind of occupation in the future. The authors conclude that in tough competition conditions in the labor market, the number of employed students, to a greater degree, characterizes the relevance of graduates of the reported profile (specialty) and from a certain university.